PEMANFAATAN BIOGAS TERMURNIKAN BERBASIS METODE KALSINASI PADA KENDARAAN BERMOTOR - Rudy S; IGB Dipa Maha Putra; Arif Mulyanto (Dinamika Teknik Mesin, 2013)
Biogas is one of the alternative energy sources that are environmentally friendly, inexpensive, easily available, renewable, and can be used as a substitute for gasoline for motor gasoline. For the use of biogas in the motor gasoline is necessary to improve the quality of biogas that is more optimal use of biogas when used as fuel.This study aims to determine the reduction of carbon dioxide (CO2) during the purification of biogas by using absorber Ca (OH)2 to the elevated levels of CH4 in biogas and its effect when testing the performance of the motor fuel, which indicate the performance of the motor fuel is the torque, power and effective specific Fuel Consumption effective. In this study, the biogas will be purified by varying the flow rate is var I (5 liters / min), var II (10 ltr / min) and var III (15 ltr / min), and biogas purification degan best quality results will be compared with biogas before purification by way of testing the motor performance in round 1500 rpm, 2500 rpm,3500rpm and 4500 rpm.The result showed that the purification of biogas menggunan Ca (OH)2 at a rate var II (10 ltr / min) produced the best biogas CH4 content of 91.0%, better than the variations I and III variations, and the results of performance testing of the motor fuel showed improvement menghasillkan better quality. Judging from rotation 4500 rpm for prior purification 5.9399 Nm torque, power and SFCe effective 2797.7079 W 0.000164 (kg / jam.W), whereas after purification 6.5821 Nm torque, effective power 3100.1628 W and SFCe 0.000113 (kg / jam.W)